Frozen section and electron microscopy studies of the infection of the red palm weevil, Rhynchophorus ferrugineus (coleoptera:curculionidae) by the entomopathogenic fungus Metarhizium anisopliae - Sun, Xiaodong (Springer International Publishing, 2016)
This study determined the pathogenicity of Metarhizium anisopliae strain SD-3 against invasive red palm weevil (RPW), Rhynchophorus ferrugineus Olivier (coleoptera:curculionidae) larvae in Hainan Province, China. Inoculation of 1 × 108 conidia/mL caused 100 % mortality of R. ferrugineus, indicating that the conidia of strain SD-3 were highly virulent. The process of invasion mechanism was showed by scanning electron microscopy (SEM) and frozen section as follows. Once R. ferrugineus was infected by strain SD-3, M. anisopliae hyphae first invaded the cuticular and body cavity of R. ferrugineus. Secondly, well-developed muscles, fat, tracheaes and digestive tube tissues in the abdomen of R. ferrugineus were then decomposed and absorbed by M. anisopliae hyphae, leading to the total destruction of the larvae. Finally, M. anisopliae hyphae reproduced, resulting in a large number of conidia in the body of RPW. The SEM and frozen section are convenient tools to observe the mode of action of entomopathogenic fungi and to observe how M. anisopliae is able to colonize and infect the host.